Oral Bacterial and Fungal Microbiome Impacts Colorectal Carcinogenesis - Klimesova, Klara; Jiraskova Zakostelska, Zuzana; Tlaskalova-Hogenova, Helena (Frontiers in Microbiology, 2018)
Host’s physiology is significantly influenced by microbiota colonizing the epithelial surfaces. Complex microbial communities contribute to proper mucosal barrier function, immune response, and prevention of pathogen invasion and have many other crucial functions. The oral cavity and large intestine are distant parts of the digestive tract, both heavily colonized by commensal microbiota. Nevertheless, they feature different proportions of major bacterial and fungal phyla, mostly due to distinct epithelial layer organizations and different oxygen levels. A few obligate anaerobic strains inhabiting the oral cavity are involved in the pathogenesis of oral diseases. Interestingly, these microbiota components are also enriched in gut inflammatory and tumor tissue. An altered microbiota composition – dysbiosis – and formation of polymicrobial biofilms seem to play important roles in the development of oral diseases and colorectal cancer. In this review, we describe the differences in composition of commensal microbiota in the oral cavity and large intestine and the mechanisms by which microbiota affect the inflammatory and carcinogenic response of the host.